FRI0402 Onset clinical involvement as prognostic factor in systemic sclerosis (SSC). (15th June 2017) - Pestaña, M Fernández; Rivas, M Rubio; Vilella, C Tolosa; Castillo, A Guillén del; Colunga, D Argüelles; Martinez, L Trapiella; Pla, V Fonollosa; Aznar, CP Simeόn; ,
Abstract : Background: In most patients with SSc, the onset is in the form of Raynaud's phenomenon (RP), but in a few is in the form of visceral or musculoskeletal involvement or skin sclerosis. Several risk factors are related to poor outcome in patients with SSc, but never before has the mode of onset been described as one of them. Objectives: To asses the mode of onset as prognostic factor in patients with SSc. Methods: A retrospective and multicentre cohort study including 1625 patients with SSc, based on the National Spanish Scleroderma Registry (RESCLE) which includes 28 referral centres. RP, puffy hands, arthralgia/arthritis, skin sclerosis, intersititial lung disease (ILD), pulmonary arterial hypertension (PAH) and esophageal hipomotility where included as clinical modes of onset. Results: The cohort was split up in two groups: 1342 patients (83%) presented as RP and 283 (17%) presented as non-RP (see graphic below) Non-RP patients where younger at onset of disease (44.7±16.5 vs 49±15.6 years, p<0.001), showed higher percentage of diffuse subtipe (36% vs 19%, p<0.001), developed more visceral involvement during the course of the illness and where more frequently anti-RNAp III positive (29 vs 10%, p<0.001). Overall mortality was 16% in patients presented as RP vs 23% in non-RP patients (p=0.003). Few differences where noted among causes of death related to SSc, but the higher mortality was observed in RP group due to PAH (19% vs 8.1%, p=0.05) and due to ILD in non-RP group (24% vs 8.3%, p=0.002). Survival of patients with RP at onset was better at anytime than those with a non-RP onset: 0.97 vs. 0.89 at 5 years, 0.93 vs. 0.82 at 10 years, 0.83 vs. 0.63 at 20 years and 0.71 vs. 0.51 at 30 years from onset (p<0.001). Conclusions: The mode of onset can be considered as independent prognostic factor, and specifically non-RP onset can be considered as a risk factor related to poorer outcome and RP onset and arthralgias can be considered as protector factors. Disclosure of Interest: None declared